The Effects of Transobturator Tape Surgery on Sexual Functions in Women With Stress Urinary Incontinence. Issue 4 (2nd September 2020) - Kizilkan, Yalcin; Tohma, Yusuf Aytac; Senel, Samet; Gunakan, Emre; Oguzulgen, Ahmet Ibrahim; Aktas, Binhan Kagan; Bulut, Suleyman; Gokkaya, Cevdet Serkan; Ozden, Cuneyt; Ozkardes, Hakan; Ayhan, Ali
Abstract: Introduction: Stress urinary incontinence (SUI) can adversely affect the patient's sexual function. Aim: To evaluate the sexual functions in women who underwent transobturator tape (TOT) surgery because of stress urinary incontinence and factors affecting the treatment results. Methods: The study was conducted in 2 tertiary level clinics between 2013 and 2019 and included sexually active patients with a diagnosis of SUI who underwent TOT operation. The preoperative and postoperative (6 months after surgery) Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire short form (PISQ-12) scores of the patients were evaluated. The patients were evaluated according to the score changes of an increased score (benefited) and the same or lower score (did not benefit). The PISQ-12 questionnaire has 3 subdomains of behavioral-emotive (Q: 1–4), physical (Q: 5–9), and partner-related (Q: 10–12). Each question is scored from 0 to 4, giving a total ranging from 0 to 48. A higher PISQ-12 score indicates better sexual function. Main Outcome Measure: PISQ-12. Results: The study included 117 patients with a median age of 52 years (range, 32–67 years), and 51.3% of the patients were postmenopausal. When the preoperative and postoperative PISQ-12 scores were evaluated in the whole group, there was a statistically significant improvement (from 24.66 to 26.52, P = .001). In the analysis of domains, there was a statistically significant improvement in physical score (from 11.68 to 13.53, P < .001), whereas behavioral-emotive and partner-related scores did not significantly change. In the multivariate analysis of menopausal status, parity and presence of diabetes mellitus were all independently and significantly associated with poor PISQ-12 outcome (OR: 2.60, 95% CI: 1.41–4.81, P = .002; OR: 1.59, 95% CI: 1.03–2.47, P = .034; and OR: 2.42, 95% CI: 1.28–4.58, P = .007, respectively). Conclusion: Both physical and psychological statuses should be taken into consideration when planning treatment in patients with urinary incontinence, and it should be noted that postsurgical sexual function status may not be positively affected in postmenopausal, multiparous, and diabetic patients.